Pengaruh Leverage, Environmental Performance, Ukuran Perusahaan, Profit Margin, dan Environmental Disclosure Terhadap Economic Performance - Ibnu Fajar Saleh; Dirvi Surya Abbas; Imam Hidayat; Ahmad Jayanih (Jurnal Ekonomi, Bisnis dan Manajemen, 2022)
The purpose of this study is to determine the effect of leverage, environmental performance, company size, profit margin, environmental disclosure on economic performance at consumer goods industrial companies listed on the Indonesia Stock Exchange (IDX). The research time period is 4 years, namely the 2016-2019 period. The population of this study includes all consumer goods industry companies listed on the Indonesia Stock Exchange (BEI) for the period 2016 2019. The total population of 56 companies using purposive sampling method obtained 14 samples of companies that meet the criteria, with a total of 56 observational data. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analysis method used is panel data regression analysis. The results showed that leverage and environmental performance had no effect on economic performance, while company size and profit margin had a positive effect on economic performance.